Tratamento tópico com o triterpeno pentacíclico uvaol acelera a cicatrização de feridas cutâneas em camundongos - Carvalho, Paulo Sérgio de Melo (2013)
Wound healing is a complex event which involves various cells and molecules capable of interacting to provide for reconstruction of the tissue. In this study we evaluated the effect of pentacyclic triterpene, uvaol, in the process of healing of experimental wounds. Thus, excisional wounds were made on the dorsum of Swiss mice, which wound contractions were evaluated under treatment with uvaol, Fibrase® or NaCl (0.9%) on different days after surgical procedure. On day 9 after surgery, uvaol treated mice showed a significant reduction in wound area compared to the controls. Histological analysis showed that uvaol was able to induce an adequate tissue organization as well as an increase in collagen deposition when compared to the group treated with saline. Furthermore, this study demonstrated that topical treatment of uvaol was not able to cause systemic toxicity in parameters determined in this study and for the duration of the healing process assessed. Moreover, this triterpene did not interfere with both animal weight and profile cell blood during the period of treatment. In vitro, uvaol was not able to induce changes in viability of human fibroblasts, indicating absence of toxic effects associated with its use. When incorporated into a cream, uvaol kept its property to heal wounds, indicating that this active ingredient retains its properties even when under pharmaceutical formulation. In addition, skin treatment on skin with this formulation did not induce changes in the treated areas, reinforcing the absence of undesirable effects associated with medication. Together, the results of this study demonstrate for the first time the healing effects of uvaol in therapy of skin wounds.